PENERAPAN MANAJEMEN STRATEGI DALAM DAKWAH NABI MUHAMMAD SAW - Antariksa, Walid Fajar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Prophet Muhammad PBUH is a role model in every aspect of life. Many valuable lessons can be learned from his life. From the point of view of strategic management, every strategic decision that has been made by Prophet Muhammad PBUH in his dakwah in all kinds of diverse internal and external environment conditions is very much in line with modern strategy management science. This article tries to explain how strategic management applied by Prophet Muhammad PBUH especially in his da'wah so that now the Islamic religion spread all over the world.